2010
DOI: 10.1007/s11010-010-0621-4
|View full text |Cite
|
Sign up to set email alerts
|

Glutamoyl diester of the dietary polyphenol curcumin offers improved protection against peroxynitrite-mediated nitrosative stress and damage of brain mitochondria in vitro: implications for Parkinson’s disease

Abstract: Oxidative/nitrosative stress plays a crucial role in Parkinson's disease (PD) by triggering mitochondrial dysfunction. Nitrosative stress is mediated by reactive species such as peroxynitrite (PN) which could damage biomolecules thereby impinging on the cellular machinery. We observed that PN (0-1000 μM) inhibited brain mitochondrial complex I (CI) activity in a dose-dependent manner with concomitant tyrosine nitration of proteins. We also observed that exposure to PN at low concentrations (62.5-125 μM) signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…This is consistent with earlier reports suggesting that curcumin contributes to neurogenesis (Kim, S. J. et al 2008, Xu, Y. et al 2007. Similarly, our laboratory also demonstrated that curcumin derivatives with improved bioavailability offers better defense against 1-methyl-4-phenylpyridinium (MPP + ) in dopaminergic neurons (Mythri et al 2011). Curcumin treatment attenuates 3-nitropropionic acid mediated oxidative stress in vivo (Kumar, A. et al, 2007).…”
Section: Effects Of Curcumin In Models Of Pdsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with earlier reports suggesting that curcumin contributes to neurogenesis (Kim, S. J. et al 2008, Xu, Y. et al 2007. Similarly, our laboratory also demonstrated that curcumin derivatives with improved bioavailability offers better defense against 1-methyl-4-phenylpyridinium (MPP + ) in dopaminergic neurons (Mythri et al 2011). Curcumin treatment attenuates 3-nitropropionic acid mediated oxidative stress in vivo (Kumar, A. et al, 2007).…”
Section: Effects Of Curcumin In Models Of Pdsupporting
confidence: 92%
“…In all these s t u d i e s , p r o t e c t i o n w a s a f f o r d e d o n l y b y p r e t r e a t m e n t w i t h c u r c u m i n p r i o r t o administration of the toxin. A recent study in our laboratory indicated that chronic dietary consumption of turmeric caused an increase in the tyrosine hydroxylase (TH) positive neurons in the SN (Mythri et al 2011). This is consistent with earlier reports suggesting that curcumin contributes to neurogenesis (Kim, S. J. et al 2008, Xu, Y. et al 2007.…”
Section: Effects Of Curcumin In Models Of Pdsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, consequent to its anti-oxidant activity, curcumin offers mitochondrial protection in peroxynitrite-mediated nitrosative stress and damage of brain mitochondria in vitro with direct therapy [4]. Meanwhile, the most compelling and pivotal rationale for the continuing use of curcumin is its extremely good safety profile.…”
Section: Mini Reviewmentioning
confidence: 99%